Highly compressed water structure observed in a perchlorate aqueous solution - Lenton, Samuel (Nat Commun, 2017)
The discovery by the Phoenix Lander of calcium and magnesium perchlorates in Martian soil samples has fueled much speculation that flows of perchlorate brines might be the cause of the observed channeling and weathering in the surface. Here, we study the structure of a mimetic of Martian water, magnesium perchlorate aqueous solution at its eutectic composition, using neutron diffraction in combination with hydrogen isotope labeling and empirical potential structure refinement. We find that the tetrahedral structure of water is heavily perturbed, the effect being equivalent to pressurizing pure water to pressures of order 2 GPa or more. The Mg(2+) and ClO(4) (−) ions appear charge-ordered, confining the water on length scales of order 9 Å, preventing ice formation at low temperature. This may explain the low evaporation rates and high deliquescence of these salt solutions, which are essential for stability within the low relative humidity environment of the Martian atmosphere.